2017
DOI: 10.1007/978-3-319-59144-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Empathic Avatars in Stroke Rehabilitation: A Co-designed mHealth Artifact for Stroke Survivors

Abstract: Stroke is the second highest cause of death and disability worldwide. While rehabilitation programs are intended to support stroke survivors, and promote recovery after they leave the hospital, current rehabilitation programs typically provide only static written instructions and lack the ability to keep them engaged with the program. In this design science research paper, we present an mHealth artifact that builds on behavior change theory to increase stroke survivors' engagement in rehabilitation programs. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…A 2021 review [ 27 ] documented the application contexts (eg, diabetes and nutrition), stakeholders (eg, caregivers, nurses, and specialists), and methods used in co-design mHealth studies, including a mapping to the Sanders and Stappers framework [ 13 ]. The methods that have been applied include cultural probes [ 28 - 31 ], storytelling [ 32 - 36 ], and journey maps [ 31 , 37 , 38 ]. The context of these applications includes both disease management and health promotion.…”
Section: Introductionmentioning
confidence: 99%
“…A 2021 review [ 27 ] documented the application contexts (eg, diabetes and nutrition), stakeholders (eg, caregivers, nurses, and specialists), and methods used in co-design mHealth studies, including a mapping to the Sanders and Stappers framework [ 13 ]. The methods that have been applied include cultural probes [ 28 - 31 ], storytelling [ 32 - 36 ], and journey maps [ 31 , 37 , 38 ]. The context of these applications includes both disease management and health promotion.…”
Section: Introductionmentioning
confidence: 99%
“…15 For example, one trial showed that a co-designed mHealth system supported stroke rehabilitation by improving communication of health advice and patient engagement. 16 A systematic literature review by Noorbergen et al 15 showed that co-designed strategies were of benefit to some rehabilitation patients. The literature emphasises early co-design and there is a paucity of research on the post-design phase.…”
Section: Open Accessmentioning
confidence: 99%
“…Moreover, persuasion can be supported by higher anthropomorphism (e.g., using detailed facial expressions). Overall, more visually realistic avatars convey stronger messages, increase the chances to persuade users (Khashe et al, 2017) and, in turn, guide behaviour (Aljaroodi, Adam, Chiong, Cornforth, & Minichiello, 2017;Noorbergen et al, 2019).…”
Section: Practical Implicationsmentioning
confidence: 99%